The plight of the onion industry in the onion capital of the Philippines: Basis for intervention strategies - Domingo, Arjhel (Asian Journal of Agriculture and Rural Development, 2023)
The study aimed to assess the plight of the onion industry in Bongabon, Nueva Ecija, dubbed the onion capital of the Philippines. The study employed a descriptive methodology. A total of 184 onion farmers from Bongabon, Nueva Ecija, served as respondents. The study revealed that most of the farmer respondents were “kasama” or tenants to the land owners. Farmers borrowed capital from trader-capitalists to finance their farm operations. Significant problems faced by onion farmers included the rising cost of farm inputs because they are imported, which could greatly affect net returns. Farm mechanization was limited, and a shortage of farm laborers was prevalent. Weather conditions and the severity of pest infestation influenced the volume of harvests. The difficulties were further aggravated by the farmers’ suspicion of price manipulation by big-time traders and unregulated importation directly competing with the price of local onions. Storing onions in cold storage facilities was the last recourse when the farmgate price was low. Based on the results of the study, intervention strategies are proposed that may be considered by concerned agencies when designing policies, programs, and projects to help the local farmers take advantage of the promising opportunities in onion growing and eventually improve the onion industry’s competitiveness in general.